Large (Ti, V) Carbonitride in Nonquenched and Tempered Steel 38MnVS6 - You Xie; Xiaoling Meng; Xiangyang Deng; Shichao Li (Advances in Materials Science and Engineering)
Large (Ti, V) carbonitrides with size even up to tens of microns in autoparts steel 38MnVS6 are studied in this work. A great number of micron-sized (Ti, V) carbonitrides are found in continuous casting billet, and the atomic ratios of V/Ti are mainly distributed in range 0.130–0.200 with an average value of 0.171. The large (Ti, V) carbonitrides have irregular morphologies, and some even have an obviously extending shape along the dendrite boundary. 3D morphologies of the large (Ti, V) carbonitride after being etched by AA solution present obvious long and flake shapes. The large (Ti, V) carbonitride has high thermal stability even at 1200°C, even though the atomic ratio of V/Ti has a decreasing tendency. There are still many large (Ti, V) carbonitrides in the rolled bar and partially broken in some which are clearly visible. According to the Thermo-Calc calculation result, the large (Ti, V) carbonitride precipitates in liquid steel during solidification. The chemical compositional characteristic is the result of subsequent mutual diffusion of elements Ti, V, C, and N. Simply reducing the content of Ti, even 13 ppm cannot eliminate the large (Ti, V) carbonitride for the nitrogen-containing, nonquenched, and tempered steel, but the quantity and size of large carbonitride are significantly reduced.